2016
DOI: 10.2337/db16-0356
|View full text |Cite
|
Sign up to set email alerts
|

FNDC5 Alleviates Hepatosteatosis by Restoring AMPK/mTOR-Mediated Autophagy, Fatty Acid Oxidation, and Lipogenesis in Mice

Abstract: Fibronectin type III domain-containing 5 (FNDC5) protein induces browning of subcutaneous fat and mediates the beneficial effects of exercise on metabolism. However, whether FNDC5 is associated with hepatic steatosis, autophagy, fatty acid oxidation (FAO), and lipogenesis remains unknown. Herein, we show the roles and mechanisms of FNDC5 in hepatic steatosis, autophagy, and lipid metabolism. Fasted FNDC5 mice exhibited severe steatosis, reduced autophagy, and FAO, and enhanced lipogenesis in the liver compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 48 publications
4
88
2
1
Order By: Relevance
“…1A). Efficiency of FNDC5 gene deletion has been identified in our recent study [25], and was further confirmed by the disappeared FNDC5 mRNA and protein expressions in the present study (Fig. 1A).…”
Section: Fndc5 Deficiency Aggravates Hfd-induced Liver Fibrosis In Micesupporting
confidence: 70%
See 1 more Smart Citation
“…1A). Efficiency of FNDC5 gene deletion has been identified in our recent study [25], and was further confirmed by the disappeared FNDC5 mRNA and protein expressions in the present study (Fig. 1A).…”
Section: Fndc5 Deficiency Aggravates Hfd-induced Liver Fibrosis In Micesupporting
confidence: 70%
“…We have shown that either FNDC5 overexpression or irisin ameliorates glucose/lipid metabolic derangements and enhances lipolysis in obesity [12]. Moreover, FNDC5 alleviates hepatosteatosis by restoring AMPK/mTOR-mediated autophagy, fatty acid oxidation, and lipogenesis in mice [13]. However, whether FNDC5 is involved in the process of liver fibrosis is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that exercise-stimulated release of irisin is independent of age or fitness level [49], although there are differences in the basal circulating irisin levels [48,49]. Accumulating evidence have shown that irisin exhibits protective effects on glucose homeostasis in obesity and T2DM, probably via the modulation of glucose and lipid metabolism in hepatic tissue and skeletal muscle [11,12,50,51]. The present study extends the previous findings via demonstrating the protective action of irisin on β-cell lipid metabolism and inflammation under type 2 diabetic condition.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the circulating levels of irisin were found to be altered in obese individuals and diabetic patients [8]; these levels were considered to be one biomarker for the prediction of the development of diabetes and mortality risk of cardiovascular diseases [9,10]. We and others have demonstrated that, in an overnutrition state, irisin can restore metabolic homeostasis, thereby alleviating insulin resistance and protecting cell function as well as survival in hepatic tissues [11][12][13]. For instance, irisin attenuated PA-induced excessive lipid accumulation in hepatocytes [13], while deficiency of FNDC5 exacerbated hepatic lipogenesis and lipid accumulation in obese mice [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation